2015
DOI: 10.1111/2041-210x.12462
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating estimators of species richness: the importance of considering statistical error rates

Abstract: 1. The performance of species richness estimators can be highly variable. Evaluating the accuracy and precision of different estimators for different assemblages is common in the ecological literature, but estimator performance is rarely measured in terms of research goals such as detecting patterns in diversity. 2. We evaluated the efficacy of nonparametric richness estimators to detect changes (i.e. type-I and type-II error rates) in species richness using two experimental designs: a block design and a trend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 56 publications
(109 reference statements)
2
35
0
2
Order By: Relevance
“…Although the method described by Chao et al (2014) is intended to estimate true richness based on coverage regardless of sequencing depth, both observed ( p < 0.001, r 2 = 0.4) and estimated richness ( p < 0.001, r 2 = 0.35) significantly correlated with library size (Supplementary Figure S5). This may indicate that the species abundance distributions vary widely among our datasets (Gwinn et al, 2016). Likewise, NMDS based on un-rarefied sequence libraries showed the influence of initial library size even after relative abundance, RLE, and TMM normalizations (Supplementary Figure S6).…”
Section: Resultsmentioning
confidence: 99%
“…Although the method described by Chao et al (2014) is intended to estimate true richness based on coverage regardless of sequencing depth, both observed ( p < 0.001, r 2 = 0.4) and estimated richness ( p < 0.001, r 2 = 0.35) significantly correlated with library size (Supplementary Figure S5). This may indicate that the species abundance distributions vary widely among our datasets (Gwinn et al, 2016). Likewise, NMDS based on un-rarefied sequence libraries showed the influence of initial library size even after relative abundance, RLE, and TMM normalizations (Supplementary Figure S6).…”
Section: Resultsmentioning
confidence: 99%
“…Gwinn, Allen, Bonvechio, Hoyer, and Beesley () found high sensitivity of bias and precision of change estimates to the relative abundances of species in a dataset. Gonzalez et al () argued that the risk of biased estimates of change needs to be considered in short time series of species richness.…”
Section: Methodsmentioning
confidence: 99%
“…Gaussian errors were assumed (Colwell et al, ) with variances specific to each year. In simple tests for a change in species richness, Gwinn et al () found inflated type I errors when using estimates of species richness as data. To limit this, the actual species counts are used as data, and their variances are modeled and kept above a minimum.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite nonparametric estimators of species richness (e.g., Chao and Jackknife estimators; see Gotelli & Chao, 2013 for a review) allow taking into account spatial heterogeneity, they are sensitive to shifts in species-abundance distribution (Gwinn, Allen, Bonvechio, Hoyer, & Beesley, 2016) and mainly structured to provide lower bound estimates of species richness at local scale (Gotelli & Colwell, 2001;Shen, Chao, & Lin, 2003). Same considerations apply when estimates are obtained by fitting asymptotic models (e.g., negative exponential or Michaelis-Menten functions; reviewed by Tjørve, 2003) to the smoothed sample-based accumulation curve, because large areas likely accumulate species at a constant or even an increasing rate due to environmental changes supporting distinctive species assemblages (Gotelli & Colwell, 2011).…”
Section: Introductionmentioning
confidence: 99%